Complementary Amplicon-Based Genomic Approaches for the Study of Fungal Communities in Humans - Heisel, Timothy (PLoS One, 2015)
Recent studies highlight the importance of intestinal fungal microbiota in the development of human disease. Infants, in particular, are an important population in which to study intestinal microbiomes because microbial community structure and dynamics during this formative window of life have the potential to influence host immunity and metabolism. When compared to bacteria, much less is known about the early development of human fungal communities, owing partly to their lower abundance and the relative lack of established molecular and taxonomic tools for their study. Herein, we describe the development, validation, and use of complementary amplicon-based genomic strategies to characterize infant fungal communities and provide quantitative information about Candida, an important fungal genus with respect to intestinal colonization and human disease. Fungal communities were characterized from 11 infant fecal samples using primers that target the internal transcribed spacer (ITS) 2 locus, a region that provides taxonomic discrimination of medically relevant fungi. Each sample yielded an average of 27,553 fungal sequences and Candida albicans was the most abundant species identified by sequencing and quantitative PCR (qPCR). Low numbers of Candida krusei and Candida parapsilosis sequences were observed in several samples, but their presence was detected by species-specific qPCR in only one sample, highlighting a challenge inherent in the study of low-abundance organisms. Overall, the sequencing results revealed that infant fecal samples had fungal diversity comparable to that of bacterial communities in similar-aged infants, which correlated with the relative abundance of C. albicans. We conclude that targeted sequencing of fungal ITS2 amplicons in conjunction with qPCR analyses of specific fungi provides an informative picture of fungal community structure in the human intestinal tract. Our data suggests that the infant intestine harbors diverse fungal species and is consistent with prior culture-based analyses showing that the predominant fungus in the infant intestine is C. albicans.